2016
DOI: 10.1590/0102-33062016abb0226
|View full text |Cite
|
Sign up to set email alerts
|

Do gender and age influence agroforestry farmers' knowledge of tree species uses in an area of the Atlantic Forest, Brazil?

Abstract: Th is study aimed to explore the extent of knowledge of tree species and their uses by agroforestry farmers in the Vale do Ribeira, Brazil, to verify whether gender and age are related to species knowledge in diff erent use categories. Th e study was conducted using semi-structured interviews, guided tours, direct observation and collection and identifi cation of botanical material. Analyses were based on the frequency with which plants were mentioned. Forty farmers (17 women and 23 men aged 18 to 78 years) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 36 publications
0
8
0
6
Order By: Relevance
“…(2006) reported that gender did not affect knowledge of plants browsed or grazed by animals, whereas Lunelli et al. (2016) and Balehegn et al. (2015) reported that it did.…”
Section: Resultsmentioning
confidence: 99%
“…(2006) reported that gender did not affect knowledge of plants browsed or grazed by animals, whereas Lunelli et al. (2016) and Balehegn et al. (2015) reported that it did.…”
Section: Resultsmentioning
confidence: 99%
“…Items' order in lists, together with the number of times the item is cited, serves to calculate the Salience Index [9,10] that determines the cultural relevance of a term or element. However, some studies use the free list without taking the Salience Index into account in their analyses and only draw items based on the cross-list frequency of the item's mentions [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…In the past decade, ethnobiology has sparked growing interest in understanding the role of diverse social, economic, and political drivers affecting local plant knowledge systems, among them gender (Ayantunde et al 2008;de Albuquerque et al 2011;Karambiri et al 2017;Luzuriaga-Quichimbo et al 2019;Montoya et al 2012), age (Bortolotto et al 2015;Brandt et al 2013;Lunelli et al 2016), socio-economic conditions (de Medeiros et al 2012;Stryamets et al 2015), religion (Bellia and Pieroni 2015;Pieroni et al 2015), and geopolitical changes (Pieroni et al 2017a;Sõukand and Pieroni 2016).…”
Section: Introductionmentioning
confidence: 99%